2021
DOI: 10.1097/ccm.0000000000005320
|View full text |Cite
|
Sign up to set email alerts
|

IV Vitamin C in Critically Ill Patients: A Systematic Review and Meta-Analysis

Abstract: To conduct a systematic review and meta-analysis to evaluate the impact of IV vitamin C on outcomes in critically ill patients. DATA SOURCES: Systematic search of MEDLINE, EMBASE, CINAHL, and the Cochrane Register of Controlled Trials. STUDY SELECTION: Randomized controlled trials testing IV vitamin C in critically ill patients. DATA ABSTRACTION: Two independent reviewers abstracted patient characteristics, treatment details, and clinical outcomes.DATA SYNTHESIS: Fifteen studies involving 2,490 patients were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
47
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 30 publications
(96 reference statements)
4
47
0
1
Order By: Relevance
“…Te meta-regression and subgroup analysis showed that the quality of studies (P � 0.04; I 2 � 77.3%) could be the primary source of the heterogeneity, while the protocol (P � 0.13; I 2 � 56.1%) and the publication year (P � 0.03; I 2 � 66.7%) could also contribute to the heterogeneity. Consistent with Patel et al [38], our subgroup analysis suggested that compared with the combination treatment group, vitamin C monotherapy showed a decreasing trend in overall mortality. However, it difered from the result of a high-quality randomized controlled study published in 2022 by Lamontagne et al [13].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Te meta-regression and subgroup analysis showed that the quality of studies (P � 0.04; I 2 � 77.3%) could be the primary source of the heterogeneity, while the protocol (P � 0.13; I 2 � 56.1%) and the publication year (P � 0.03; I 2 � 66.7%) could also contribute to the heterogeneity. Consistent with Patel et al [38], our subgroup analysis suggested that compared with the combination treatment group, vitamin C monotherapy showed a decreasing trend in overall mortality. However, it difered from the result of a high-quality randomized controlled study published in 2022 by Lamontagne et al [13].…”
Section: Discussionsupporting
confidence: 91%
“…Te primary outcome analysis showed that IV vitamin C tended to reduce overall mortality in patients with sepsis compared with the control group. However, the diference between the two groups was not statistically signifcant (Figure 3), which is consistent with the result of Patel et al [38]. Te heterogeneity among the included studies was signifcant.…”
Section: Discussionsupporting
confidence: 90%
“…Judicious interpretation of the findings of the current meta-analysis is required because of its limitations. First, the heterogeneity from our inclusion of patients with and without sepsis/septic shock as well as our definition of critically ill individuals as those whose mortality rate was higher than 5% in the control group based on a previous study (16) may bias our findings. Nevertheless, the heterogeneity was low in our mortality rate, indicating a low risk of bias.…”
Section: Discussionmentioning
confidence: 99%
“…Our subgroup analysis focusing on dosage suggested a favorable outcome associated with a low dosage of vitamin C, highlighting a 10.3389/fnut.2023.1094757 need for further research on this issue. Third, we did not investigate the efficacy of vitamin C-based combination therapy as several meta-analyses have addressed this issue (16). Finally, despite the demonstration of a gender difference in the beneficial impact of vitamin C on disease severity (i.e., acute respiratory tract infections) (46), we are unable to analyze gender-related outcomes because of a lack of relevant data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation